Widely targeted metabolomics characterizes the dynamic changes of chemical profile in postharvest peanut sprouts grown under the dark and light conditions. (December 2021) - Xiao, Yuan; Liu, Hao; Li, Haifen; Liu, Qinjian; Lu, Qing; Varshney, Rajeev K.; Chen, Xiaoping; Hong, Yanbin
Abstract: Peanut sprouts (PSs) are edible food with a high nutritional value. It is well known that different light treatments during seedling germination affect the nutritional elements of PSs. However, the comprehensive exploration of the chemical profile variation after light and dark treatments is not widely used in PSs due to the lack of high-throughout examination technology. In the present study, a widely targeted method based on UHPLC-QTRAP-MS/MS equipment was carried out to identify and screen differential metabolites. A total of 797 metabolites were identified from PSs, and 97 differential metabolites were screened between light and dark treatment groups. The majority of phytochemical compounds, such as flavonoids, alkaloids, nucleotides, amino acids, saccharides, and alcohols, were significantly up-regulated in PSs germinated under the dark conditions, which were positively related to the large-scale metabolic data of human diseases by KEGG metabolic pathway analysis. Collectively, our data suggest that the seeds should be protected from exposure to light during PS germination, which might improve the nutritional value of the final peanut product. Highlights: Chemical variations in peanut sprouts were studied by widely targeted metabolomics. Ninety-seven metabolites were identified as key chemical markers. The majority of compound levels increased after dark treatment.